2020
DOI: 10.3390/ijerph17207629
|View full text |Cite
|
Sign up to set email alerts
|

The Quality, Readability, Completeness, and Accuracy of PTSD Websites for Firefighters

Abstract: Firefighters appear at an increased risk for post-traumatic stress disorder (PTSD). Because of PTSD-related stigma, firefighters may search for information online. The current study evaluated the quality, readability, and completeness of PTSD online resources, and to determine how the online treatment recommendations align with current evidence. Google.ca (Canada) searches were performed using four phrases: ‘firefighter PTSD’, ‘firefighter operational stress’, ‘PTSD symptoms’, and ‘PTSD treatment’. The 75 webs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 48 publications
5
14
0
Order By: Relevance
“…Participants not only agreed on the usefulness of these educational principles in addressing stigma but also agreed with principles that would make educational messages accurate, reliable, and non-judgmental. This reinforces earlier studies that suggest that educational messages that are accurate, reliable, credible, and non-judgmental are crucial for addressing stigma [37,38].…”
Section: Discussionsupporting
confidence: 89%
“…Participants not only agreed on the usefulness of these educational principles in addressing stigma but also agreed with principles that would make educational messages accurate, reliable, and non-judgmental. This reinforces earlier studies that suggest that educational messages that are accurate, reliable, credible, and non-judgmental are crucial for addressing stigma [37,38].…”
Section: Discussionsupporting
confidence: 89%
“…Almost 98% of the current sample of correctional workers reported at least one correctional-specific PPTE exposure over the course of their career, which is much higher than the frequency of PPTE exposures for the general population, where 50%–90% experience one or more PPTE in their lifetime (Carleton et al, 2019; Kilpatrick et al, 2009; Ricciardelli et al, 2022), and the relative difference is consistent with PPTE exposure reports from other PSP as compared to the general population (Carleton et al, 2019). High levels of correctional-specific PPTE exposures are particularly concerning given the relationship between PTSD (Hilton et al, 2021; Killip et al, 2020; Lambert & Hogan, 2018) and other mental health disorders, such as MDD and GAD. PPTE exposures increase the odds of screening positive for several mental disorders, including PTSD, MDD, GAD, and any positive mental disorder screen.…”
Section: Discussionmentioning
confidence: 99%
“…Chi et al [ 10 ] concluded that doctors could improve the way they explained therapies with the knowledge on information patients read online [ 10 ]. DISCERN was employed also by Killip et al [ 47 ] in their study on the quality, readability, completeness, and accuracy of PTSD (post-traumatic stress disorder) websites for firefighters.…”
Section: Theoretical Backgroundmentioning
confidence: 99%